Study on the Antipyretic and Anti-inflammatory Mechanism of Shuanghuanglian Oral Liquid Based on Gut Microbiota-Host Metabolism - Gao, Yan; Liu, Lu; Li, Chen; Liang, Yu-Ting; Lv, Jing; Yang, Long-Fei; Zhao, Bo-Nian (Frontiers in Pharmacology, 2022)
Nowadays, there has increasing awareness that the therapeutic effects of natural medicines on inflammatory diseases may be achieved by regulating the gut microbiota. Shuanghuanglian oral liquid (SHL), the traditional Chinese medicine preparation, has been shown to be effective in clearing heat-toxin, which is widely used in clinical treatment of respiratory tract infection, mild pneumonia, common cold with wind-heat syndrome. Yet the role of gut microbiota in the antipyretic and anti-inflammatory effects is unclear. In this study, a new strategy of the 16S rRNA gene sequencing and serum metabolomics that aims to explore the role of SHL in a rat model of systemic inflammatory response induced by lipopolysaccharide would be a major advancement. Our results showed that the gut microbiota structure was restored in rats with inflammation after oral administration of SHL, thereby reducing inflammation. Specifically, SHL increased the relative abundance of Bacteroides and Faecalibacterium and decreased the abundance of Bifidobacterium, Olsenella, Aerococcus, Enterococcus and Clostridium in the rat model of inflammatory disease. Serum metabolomic profile obtained by the orbitrap based high resolution mass spectrometry revealed significant differences in the levels of 39 endogenous metabolites in the inflammatory model groups, eight metabolites of them almost returned to normal levels after SHL treatment. Correlation analysis between metabolite, gut microbiota and inflammatory factors showed that the antipyretic and anti-inflammatory effects of SHL were related to the recovery of the abnormal levels of the endogenous metabolites (N-acetylserotonin and 1-Methylxanthine) in the tryptophan metabolism and caffeine metabolism pathway. Taken together, these findings suggest that the structural changes in the gut microbiota are closely related to host metabolism. The regulation of gut microbiota structure and function is of great significance for exploring the potential mechanism in the treatment of lipopolysaccharide-induced inflammatory diseases with SHL.